Steady state visual evoked potential based BCI as control method for exoskeleton: A review - Ahmad, N.; Ghazilla, R.A.R.; Md Azizi, M.Z.H. (Malaysian Public Health Physicians Association, 2016)
Brain Computer Interfaces (BCI) provide a vast possibility in enabling the brain to communicate directly with the computer, hence providing an alternative in controlling the machines without much effort. In fields of rehabilitations robotics, the applications of an exoskeletons in assisting a spinal cord injured (SCI) patients were growing. Steady state visually evoked potentials (SSVEP) based BCIs that utilizes the human visual reactions to the constant flickered stimulus quickly showed its potentials among the BCIs used in rehabilitations devices because of its advantages such as a higher immunity to noises and artefacts and also its robustness compared to other BCIs. Rehabilitation exoskeletons demands an approach that are more user friendly and the aspects of control scheme and mechanical parts that are more focused on assisting the patients in rehabilitations and providing a SCI patients an alternatives to explore their surroundings in a more intuitive ways. This paper highlights the current development trends in SSVEP based BCIs for rehabilitation exoskeletons and proposed the potential research scopes in the future that can improve the effectiveness, and its potential applications in rehabilitations.